The Effectiveness of Technology Based Internship Programs in Improving the Skills of Industrial Technology Vocational School Students - Widjaja, Warkianto (Universitas Pendidikan Ganesha, 2025)
The lack of human resource capabilities in industrial technology has an impact on the lack of development of real industrial needs. The urgency of researching the need for human resources in facing advanced industrial technology projects. Therefore, this study aims to evaluate the factors that influence the obstacles and difficulties of technology-based industrial internship programs in implementing practical practices in the field. The method used is a quantitative survey type. The sample amounted to 450 industrial engineering students who were selected randomly. The data collection technique was done through an online questionnaire based on a Likert scale of 36 items. The data analysis technique used descriptive statistics, assisted by SPSS Version 29.0. With the DIF test, factor analysis, and reliability. The study's results indicate that obstacles and difficulties in program implementation are inadequate preparation, minimal industry involvement, and inadequate quality of project internships. However, programs with technology assistance were effective in improving future skills. Technology-based internship programs can address competency gaps by providing relevant hands-on experience recommendations, increasing industry collaboration, and supporting training in using technology as practical steps. The implications of this study indicate that technology integration in internship activities can be a significant strategy to bridge the gap between student competencies and industry needs.